Hearing Preservation With Standard Length Electrodes in Pediatric Cochlear Implantation. Issue 9 (October 2018) - Manjaly, Joseph G.; Nash, Robert; Ellis, Wayne; Britz, Anzel; Lavy, Jeremy A.; Shaida, Azhar; Saeed, Shakeel R.; Khalil, Sherif S.
Abstract : Objective: Preserving low frequencies following cochlear implantation improves outcomes and allows patients to use a combination of electrical and acoustic stimulation. This importance has been reflected in advances in electrode design and refined surgical techniques. Full insertion of standard length electrodes may be advantageous over shortened electrodes because more electrodes can be activated over time if low frequency hearing loss progresses. Surgeons must counsel patients over this choice but data is lacking regarding the degree and likelihood of hearing preservation achievable with standard length electrodes in children. We report our experience using standard length cochlear implant arrays for hearing preservation in children. Methods: Retrospective case series. Inclusion criteria: preoperative hearing ⩽85 dB HL at 250 Hz and aged ⩽18 years. Hearing preservation percentages are calculated using the HEARRING group formula. Preservation of > 75% was considered complete, 25 to 75% partial, and 1 to 25% minimal. Patients were implanted with either MED-EL FLEX28 or Cochlear Nucleus CI522. Standardized operative technique with facial recess approach, posterior tympanotomy and minimally traumatic round window insertion. Results: Fifty-two implantations in 27 pediatric patients met inclusion criteria. Mean age at implantation: 9.8 years. Average latest audiogram: 8 months. Mean total pre- and postoperative pure-tone averages were 82.8 and 92.6 dB. Seventeen (33%) ears demonstrated complete hearing preservation, 22 (42%) ears partial hearing preservation, 7 (13%) minimal hearing preservation, and 6 (12%) exhibited no acoustic hearing postoperatively. Mean hearing preservation was 55.5%. Conclusion: Hearing preservation is achievable to varying degrees in pediatric cochlear implantation using standard length electrodes though it is difficult to predict preoperatively which children may benefit. This study is among the largest additions to the knowledge base for this patient group.